A Scientific Way to Solve Environmental Issues is a Theory Research - Karzan Qader Hamad; Dana Lateef Jalal (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Environmental sociology, one of the most important new and important branches of social literature, entered universities in the 1970s and was presented as an academic branch of framework, style and modus operandi. At the University of Kurdistan, it has been included in the academic and value education programme over the past few years. This scientific branch participates in the relationship between society and the environment, with the exception of discussing the Internet and discussing the most important types of environmental pollution. In addition to discussing issues related to the environment and society, environmentalism also offers a scientific way to find and find solutions to environmental problems and issues. Our question in this research is whether environmental sociology in Kurdistan can be an important tool for solving environmental problems? Is it forbidden in Kurdistan to find a solution to the causes of environmental pollution in Kurdistan? To answer these questions, try to show the context of introducing theoretical aspects of environmental and social relationships to return to the method of content analysis and side analysis.